Tribocorrosão do aço inoxidável martensitico AISI 420 cementado por plasma a baixa temperatura: sinergia erosão-corrosão - Mainardi, Vinícius Almeida (2023)
ibocorrosive performance of AISI 420 martensitic stainless steel. The study is structured in two parts. In the first part, experiments were conducted to assess the impact of erosion test parameters, including impact velocity, impact angle, and exposure time, on the performance of both carburized and non-carburized steel (reference condition). Both types of erosion, solid particle erosion and liquid impingement erosion, were employed using distilled water and saline solution as fluids. This initial approach allowed evaluating the effects of these parameters on the material's erosion behavior and determining the combination that produces a tribosystem with greater severity. Once the most severe erosive condition was defined, the second part of the study addressed the comparative evaluation of the erosion-corrosion behavior of treated and untreated materials through electrochemical tests simulating liquid impingement impact and with solid particles slurry conditions. Comparing the performance of the untreated sample with those subjected to the carburizing process, a significant improvement in wear resistance and corrosion of carburized AISI 420 steel was observed. The observed performance enhancement can be attributed to the formation of the carburized layer, composed of the α'C and Fe3C phases. The results of the first phase indicated that the tribosystem's severity was significantly affected by the test conditions. There was a marginal increase with the introduction of saline solution, while the presence of solid particles resulted in a more substantial increase. Mass loss demonstrated a proportional increase with the impact velocity and impact angle. Regarding the exposure time, mass loss curves varied according to the test environment. In this case, for solutions containing solid particles, an additional final stabilization stage was observed, in addition to the incubation and acceleration stages identified in the absence of abrasives. In the second phase of the study, it was observed that slurry impact erosion and liquid impingement erosion resulted in an increase in corrosion current density and a decrease in corrosion potential. The Ω and Ω' parameters (indicators of the influence of carburizing on the relationships between 'slurry erosion and corrosion' and 'liquid impingement erosion and corrosion' mechanisms, respectively) showed that carburizing mitigates the impact of both erosion modes on material degradation. Additionally, carburizing treatment reduced corrosion rate, total mass loss, and erosion-induced mass loss in treated samples, minimizing the synergy between erosion and corrosion. Furthermore, interactions between degradation modes indicate that erosion predominantly governs the deterioration process of AISI 420 steel. In conclusion, the results presented confirm the potential of plasma carburizing treatment to enhance the tribocorrosion resistance of AISI 420 steel.